A case of initiator-leadership and follower-leadership - Alvesson, Mats, 1956- ([London] : SAGE, 2016)
This case study presents a historical overview of a Swedish computer consultancy company's leadership model, including the founders and public figures that contributed to the company's growth. This case helps the reader to understand the relationship between organizational culture and leadership.
Originally Published in: Alvesson, M. (2012). A Case of Initiator-Leadership and Follower-Leadership. In Understanding organizational culture (2nd ed., pp. 115-120). London: SAGE Publications Ltd. ISBN: 9780857025586.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Leadership -- Case studies; Corporate culture -- Case studies